Rapid and specific labeling of single live Mycobacterium tuberculosis with a dual-targeting fluorogenic probe - Yunfeng Cheng; Jinghang Xie; Kyung Hyun Lee; Rajiv L. Gaur; Aiguo Song; Tingting Dai; Hongjun Ren; Jiannan Wu; Zhaogang Sun; Niaz Banaei; Demir Akin; Jianghong Rao (2018)
A dual-targeted fluorogenic probe and microfluidic chip enables single-cell labeling and quantification of live Mycobacterium tuberculosis .